Three Approaches to Dance History A Review Article - Kant, Marion 1951- (Edinburgh: Edinburgh University Press, 2011)
RESUMEN: Lynn Garafola, Legacies of Twentieth Century Dance. Middleton Conn: Wesleyan University Press 2005. 445 pp, index. Ivor Guest, The Paris Opera Ballet. Alton Hampshire: Dance Books 2006. 150 pp, appendices, index. Marina Grut, The Royal Swedish Ballet. History from 1592 to 1962. Hildesheim, Zurich, New York: Georg Olms 2007. 706 pp, index, appendices [pp. 505-685] These three books have little in common; that they make an appearance in one review is pure coincidence. Lynn Garafola employs analytical dance historical methods with an acute sense of the implications of theoretical frameworks, Ivor Guest provides an example of empiricist scholarship as does Marina Grut. The latter believes in history as an accumulation of rich documentation that is self-selecting (through time) and self-evident as well as self-explanatory (through its written content). Guest focuses on an institution that came to represent an era of dance whereas Grut writes about an institution that happened to represent a national empire.